À sombra desta mangueira: Ocupação Guarani Kaiowá sob protagonismo infantil - Frederico Alves Lopes (2019)
What are the children role on the fight for land and residence? We present an analyze about the Occupation Guarani Kaiowá, localized on Comunidade/MG, starting from the child protagonism. The children GK work without forgive the study, play at the same time that they fight, relating affectively with the mango tree, place of jokes and meetings, fresh shadow, politics decisions, parties and communion, finally, place of the own life community that exist and resist. The results were obtained since the participants observations, interviews, questionnaires, bibliography and documental analysis, photo and video workshops and mainly of the results checking together with the participants. Factors that remain us to conclude that the Guarani Kaiowa Occupation is an utopia land, because materialize beyond all difficulties, the right to home without overlook that the land belongs to who make it alive.